Nasal High-Frequency Oscillatory Ventilation vs. Nasal Continuous Positive Airway Pressure as Therapy for Postextubation Respiratory Failure in Infants After Congenital Heart Surgery - Wu, Hong-Lin; Lei, Yu-Qing; Xie, Wen-Peng; Chen, Qiang; Zheng, Yi-Rong (Frontiers in Pediatrics, 2021)
Objective: This study aimed to evaluate the effects of nasal high-frequency oscillatory ventilation (NHFOV) vs nasal continuous positive airway pressure (NCPAP) on postextubation respiratory failure (PRF) in infants after congenital heart surgery (CHS). Method: Eighty infants underwent postoperative invasive mechanical ventilation for more than 12 hours and planned extubation. The infants were randomized to undergo either NHFOV or NCPAP after extubation. Primary outcomes were the incidence of PRF and reintubation, the average PaCO2 level, the average oxygenation index (OI), and pulmonary recruitment in the early extubation phase. Secondary outcomes included the NCPAP/NHFOV time, length of hospital stay, treatment intolerance, signs of discomfort, pneumothorax, adverse hemodynamic effects, nasal trauma and mortality. Results: Except for PaCO2 within 12 after extubation (39.3 ± 5.8 vs 43.6 ± 7.3 mmHg, p=0.05), there was no statistically significant difference for any of the primary outcome measure (PRF, reintubation within 12 h after extubation, oxygenation index within 12 h after extubation, or lung volumes on X-ray after extubation) or secondary outcome measures (duration of non-invasive ventilation, duration of hospital stay, ventilation intolerance, signs of discomfort, pneumothorax, nasal traum, adverse hemodynamic effects, or death prior to discharge), p>0.1 for each comparison. Conclusion: NHFOV therapy after extubation in infants after CHS was more efficient in improving CO2 cleaning than NCPAP therapy, but there was no difference in other outcomes (PRF, reintubation, oxygenation index and pulmonary recruitment.).